Pengaruh Rasio Profitabilitas Terhadap Harga Saham Syariah Yang Terdaftar Di Jakarta Islamic Index (Pada PT. Ace Hardware Indonesia Tbk Periode 2014-2022) - Rena Rosnawati; Ahsan Putra; Mohammad Orinaldi (Politeknik Kampar, 2023)
This study used a quantitative approach. The sample in this study used quarterly data at PT. Ace Hardware Indonesia Tbk for the 2014-2022 period is 32 samples. The independent variable in this study is profitability (X) proxied on Return On Asset (ROA) and Return On Equity (ROE). The dependent variable is the stock price (Y). The data used in this study are secondary data. This study used multiple linear regression analysis methods and hypothesis testing of t test and f test. The tool used is the SPSS program version 25. Result This research shows that Return On Asset (ROA) and Return On Equity (ROE) affects stock prices using the f test on the independent variable has a simultaneous influence on the dependent variable. The calculation of the coefficient of determination shows that all variables are independent Return On Asset (ROA) and Return On Equity (ROE) can explain the stock price variable by 33.8%.